Islands as Time Capsules for Genetic Diversity Conservation: The Case of the Giglio Island Mouflon - Mario Barbato; Marco Masseti; Monica Pirastru; Nicolò Columbano; Monica Scali; Rita Vignani; Paolo Mereu (Diversity, 2022)
The use of multidisciplinary approaches of investigation including biological, biogeographical, historical, morphological, and genetic analysis, can be useful in identifying and preserving biodiversity. The present study focuses on the characterisation and conservation of a mouflon population (Ovis gmelini musimon) from the Mediterranean island of Giglio. Here we provide the first molecular data on the Giglio population and compare it with mouflons from Sardinia, Elba, and Corsica using both nuclear and mitochondrial markers. Our results suggest that the Giglio mouflon harbours genetic variability likely of Sardinian origin but not represented in the current Sardinian mouflon diversity. Although not presenting the typical characteristics of an invasive alien species, the Giglio mouflon is being subjected to eradication through culling or trapping and surgical sterilization. The molecular evidence we report highlights that such actions are causing the irremediable loss of ancestral genetic variants of the genus Ovis. Finally, we highlight how a multidisciplinary approach is necessary to aid the conservation and management of the anthropochorous populations of Mediterranean mammals.